(untitled) (Global Journal of Management and Business Research, 2022)
The global growth rate of equity crowdfunding of which Crowdfarming is a brand has surpassed the projected limits. Crowdfarming serves as alternative finance and platform for interested small scale investors in farming in many countries. This Paper investigates the diversity of crowdfarming platforms among investors in all the five administrative divisions of Lagos state. Three hundred participants were selected using purposive sampling techniques and used for the study. The data were summarized using frequencies and percentages, while Shannon Entropy Index was applied to analyse the diversity of crowdfarming among participants in the administrative divisions. The results showed majority of the participants were male (59%) with average family size of all crowdfarming participants being 5.83. Average household size was highest in Lagos Island (Eko) (7) and Epe (7) and lowest in Ikeja (4). Younger respondents (22- 55 years) constitute the majority of crowdfarming participants (72%). Average total amount invested was #566,634; highest in Ikeja (#230,000) and lowest in Epe (#95,155). Thus showing high rate of investment flow to crowdfarming. The Shannon diversity index was 1.16 depicting crowdfarming platforms were evenly distributed across the state. Ikeja and Badagry have uniform diversity of Crowdfarming participants (H=1.07), followed by Ikorodu (H=0.89). Lagos Island has the lowest diversity (H0.80). Even distribution of crowdfarming platforms investment should signal improved monitoring for financial security of Lagosians; and eye-opener to step up measures to stem or prevent market failures.